Modern studies of the cryosphere of the Zeravshan and Gissar Ranges (Tien Shan) - Frolov D M; Koshurnikov A V; Gagarin V E; Dodoboev E I; Nabiev I A (E3S Web of Conferences, 2023)
The paper presents brief results of the modern studies of the cryosphere of the Zeravshan and Gissar ranges. Also the rate of decrease in the area of glaciers over the last almost a hundred years and the presence and degradation of permafrost during that time were considered. The actual description of the methodic for estimation of the depth of the ground freezing based on air temperature and snow thickness data were also given. An experience of application of this method for estimating the depth of ground freezing on the mountain slopes in order to compile the maps of the permafrost zone of the Zeravshan and Gissar ranges was described.